Identification and molecular characterization of a putative heme ABC transporter in Neisseria meningitidis - Ingrey, Keely (University of Ottawa (Canada), 2010)
A detailed mechanism for heme uptake in pathogenic Neisseriae has not yet been elucidated. Once heme is deposited in the periplasmic space, a heme dedicated ABC transporter has been hypothesized to convey heme into the cytoplasm. To address this hypothesis, we used several molecular techniques to identify and characterize a putative heme ABC transporter in Neisseria meningitidis. Using 2-D gel electrophoresis, we identified six proteins with increasing expression under heme-limiting conditions. Although these proteins appear to be iron-regulated, the genes encoding these proteins are not associated with periplasmic components of ABC transporters. Using DNA microarray analysis, we identified eleven ABC transporter components. A mutation in one of these genes, the ATPase NMB1993, was constructed. No difference in the ability of various iron sources to support the growth of the mutant and wild-type strains was observed under iron-restrictive conditions. No difference in growth rates between the two strains was discerned, suggesting no role in heme metabolism. Another uncharacterized putative periplasmic component, NMB0586, exhibited 27% amino acid identity to a recently characterized periplasmic heme-binding protein in the Haemophilus ducreyi transporter. To address its role in heme metabolism, NMB0586 was disrupted by insertional inactivation. The ability of various iron sources to support the growth of the mutant and wild-type strains was compared under iron-restrictive conditions. The mutant failed to display a heme-deficient phenotype. However, in view of the recognized degenerate binding specificity of the permease component of some ABC transporters, the heme-binding property of NMB0586 was studied. Purified NMB0586 bound to heme at a concentration of 10-4 M, using enhanced chemiluminescence. Furthermore, the binding of purified NMB0586 protein to hemin-agarose demonstrated concentration dependent binding. However, increasing concentrations of competing heme ligand did not result in a decrease in NMB0586 protein binding to hemin-agarose. NMB0586 was also unable to functionally complement a heme-deficient mutant of Escherichia coli. These findings suggest that NMB0586 is unlikely involved in heme acquisition in meningococci. In conclusion, this study describes the difficulties in identifying a meningococcal heme ABC transporter, but highlights several techniques for the future identification and characterization of a heme ABC transporter in Neisseriae.
Keywords: Biology, Microbiology.